Isidore of Seville and the "Liber Iudiciorum": the struggle for the past in the Visigothic Kingdom - Kelly, Michael J. (The medieval and early modern Iberian world, 2021)
Introduction : the Isidore-moment, the Liber Iudiciorum, and the schools thesis -- In the beginning : the historyof the historiography of Isidore -- Origins and histories : creating new chains of signification -- The historical Lacunae and Damnatio[nes] Memoriae of the Hispana -- Pinnacle and twilight : the Liber Iudiciorum and the "historical" fulfillment of the Isidore-moment -- Conclusion.